If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7x + 5 = 11 + -1x Reorder the terms: 5 + 7x = 11 + -1x Solving 5 + 7x = 11 + -1x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add 'x' to each side of the equation. 5 + 7x + x = 11 + -1x + x Combine like terms: 7x + x = 8x 5 + 8x = 11 + -1x + x Combine like terms: -1x + x = 0 5 + 8x = 11 + 0 5 + 8x = 11 Add '-5' to each side of the equation. 5 + -5 + 8x = 11 + -5 Combine like terms: 5 + -5 = 0 0 + 8x = 11 + -5 8x = 11 + -5 Combine like terms: 11 + -5 = 6 8x = 6 Divide each side by '8'. x = 0.75 Simplifying x = 0.75
| -6+4(1-v)=-3(v+2) | | -2x+7=8-(1+4x) | | 4x45/6 | | 2-3z=7(8-2z)+12 | | -11-9+0=-20 | | .5(6)+y=1 | | 3(h+5)=3h+15 | | 8x-25=2-3x+5-5x | | 3(2q+7)=15(p-4) | | -(x+8)+1=5(7-3x) | | 2+(-9)-(-4)= | | -69=7v-5 | | (r+5/3)=20 | | -6y-2=3-5y | | 4m+8+5(3m-5)-5(m+5)=0 | | 2y-6=5y+6 | | (X-3)x=550 | | 7-3x=7-4x+x | | 2x-2=18x+6 | | 30+34-x=13x-5x+37 | | 2z+5=4x-9 | | 1-(-4-n)=3(n+3) | | 5x^2+20xy-40y= | | 9-(-9)+(-4)= | | x+2x+6x+3=21 | | 4y^3-5y^2-12y+15= | | Y(7+3)=5 | | (-7)+2+(-5)= | | -2(1-3x)-x=-2-6x | | 4y^3-5y^2-12y-15= | | 5(a-12)+(2a+15)=a-9 | | 8x-7x=-(1-2x)-7(x+5) |